The Implementation of Cognitive and Metacognitive in Critical Listening Skill through a Short Video - Susanti, Susanti; Sinaga, Juwita Boneka; Ashari, Erwin (Lectura : Jurnal Pendidikan, 2025)
The development of critical listening skills is essential for university students to engage effectively with complex academic content, fostering higher-order thinking and problem-solving abilities. Critical listening involves actively analyzing, synthesizing, and evaluating information. This study explores the integration of cognitive and metacognitive strategies to enhance critical listening among third-semester students. Cognitive strategies focus on mental processes, while metacognitive strategies involve self-regulation and reflection. Multimedia tools, particularly short videos, offer dynamic platforms to facilitate active engagement and critical thinking. Research suggests that multimedia learning increases metacognitive awareness and deepens cognitive processing. The study further examines discovery learning's role, which emphasizes metacognitive strategies to promote autonomous learning and critical thinking. Despite growing interest in multimedia's impact on language learning, limited research addresses the integration of short videos with cognitive and metacognitive strategies for developing critical listening. This study aims to fill this gap by highlighting the potential of multimedia-supported strategies to enhance students' critical listening competence, fostering their academic success and reflective learning processes.